Give Refuge to the Stranger : the Past, Present and Future of Sanctuary - Rabben, Linda, 1947- (Left Coast Press, 2011)
The concept of sanctuary - giving refuge to the threatened, vulnerable stranger - is universal and older than human society. From its origins in primate populations, to its elaboration in ancient religious traditions, to the modern legal institution of asylum, Linda Rabben tells the story of sanctuary as it evolved over thousands of years. She then examines asylum today, analysing policy in the US, Canada, Europe, and Australia and linking them to the experiences of courageous individuals to show how immigration and asylum are under attack in around the world. Her expert account offers.